OPTIMIZING TOURIST SATISFACTION AT MOJOKERTO'S PACET SPECIAL MARKET THROUGH LOCATION, ATTRACTION AND SOCIAL MEDIA PROMOTION - Ardi Dwi Aditya; Sri Andayani; Ute Chairuz M. Nasution (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This research aims to examine the influence of location, attractiveness and social media promotion on tourist satisfaction at Pasar Keramat Pacet, Mojokerto. Indonesia, with more than 17,540 islands and diverse cultural riches, is a popular tourist destination. In the first semester of 2023, 433.57 million domestic trips were recorded, with East Java contributing 116.7 million visits. Mojokerto Regency, especially Kramatjetak Village in Pacet District, has interesting tourism potential such as